La fine del mondo. Geofilosofia della catastrofe ambientale - Resta, Caterina (Bollettino Filosofico, 2023)
Beyond the persistent denialism, the ecological catastrophe is not the pessimistic prognosis of Cassandra, but a merciless diagnosis of the state of planetary health, which is supported by scientific data. It cannot simply be considered a crisis of the environment, as if it were only a process affecting nature; in the age of the Anthropocene, it is clear that ecological disaster is the result, the product, of man’s actions, due to his unbalanced relationship with the environment in which he lives. Its premise is the “calculative thinking” that has characterised Western rationality since the Modern Age and the scientific revolution, from which comes a development model that has now become unsustainable. Only a radical turnaround and an overall change in our way of life can perhaps prevent the imminent extinction of the human species. We should reconsider the Earth as Ecumene (Berque), as a World in which we co-habit together with other living beings, entering into a new pact of alliance with the biosphere. Only a Constitution of the Earth (Ferrajoli), capable of guaranteeing the protection of the environment and the inalienable common goods that are essential to humankind’s survival, could adequately face the challenge of a global world that is destined for catastrophe. Keywords: Anthropocene, Earth Constitution, Ecumene, Environmental Catastrophe, Calculative Thinking